The Effect of Epistemic Value on Tourists Revisit Intention in Lake Toba with Satisfaction as Mediation Variable - Saragih, Megasari Gusandra; Surya, Elfitra Desy; B, Mesra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The influence of epistemic value on the interest of returning tourists to the super priority tourist attraction of Lake Toba with satisfaction as a mediation is very important to be studied during this covid 19 pandemic. The number of samples as many as 110 respondents with the sample withdrawal technique is purposive sampling. The analytical model used is path analysis and Sobel Test with an analytical tool. The study results found that epistemic Value had a significant impact on tourist satisfaction; epistemic value and satisfaction affected the interest of returning tourists to the super-priority tourism of Lake Toba. Satisfaction mediating partial mediation is the effect of epistemic Value on the welfare of returning tourists to the super-priority tourism of Lake Toba.